Student’s Mental Model using Four-Tier Diagnostic Test on Acid-Base - Suci Rahmadani; Fajriah Azra (Journal of Educational Chemistry (JEC), 2025)
The purpose of this study was to describe the mental model of students on the acid-base material class XI phase F. The type of research used is descriptive research with a quantitative approach. The research population consisted of students in class XI Phase F, and the research sample comprised 31 students from XI F9 at SMAN 2 Payakumbuh, using a purposive sampling technique. The data collection technique was conducted in two stages: the test stage and the interview stage. This test stage utilises a four-tier diagnostic test instrument, employing three levels of chemical representation. Then, the interview stage is conducted to gather data and confirm the results of the diagnostic tests that have been performed. The findings of this study detected that students have varied mental models. There are 41.1% have a mental model of synthesis-partial understanding B; 19.6% synthesis-partial understanding A; 15% initial model; 12.5% scientific model, and 11.8% synthesis-misconception. This is supported by the presentation agreement of the interview result with the diagnostic test.